2019
DOI: 10.48550/arxiv.1902.02971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flexibility of triangle-free planar graphs

Zdeněk Dvořák,
Tomáš Masařík,
Jan Musílek
et al.

Abstract: Let G be a planar graph with a list assignment L. Suppose a preferred color is given for some of the vertices. We prove that if G is triangle-free and all lists have size at least four, then there exists an L-coloring respecting at least a constant fraction of the preferences. * Work on this paper was supported by project 17-04611S (Ramsey-like aspects of graph coloring) of Czech Science Foundation.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The same is true for C 6 -free planar graphs [7]. For C 3 -free graphs, Dvořák, Masařík, Musílek, and Pangrác [4] showed that they are weighted ε-flexible for lists of size 4 and that this the result is tight. Surprisingly, the discharging proof in [4] is quite involved compared to the easy observation that C 3 -free planar graphs are 3-degenerate, which implies 4-choosability.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…The same is true for C 6 -free planar graphs [7]. For C 3 -free graphs, Dvořák, Masařík, Musílek, and Pangrác [4] showed that they are weighted ε-flexible for lists of size 4 and that this the result is tight. Surprisingly, the discharging proof in [4] is quite involved compared to the easy observation that C 3 -free planar graphs are 3-degenerate, which implies 4-choosability.…”
Section: Introductionmentioning
confidence: 76%
“…The concept of ε-flexibility was introduced by Dvořák, Norin, and Postle [6]. Subsequently, it was studied for various sub-classes of planar graphs, e.g., triangle-free [4], girth six [5], or C 4 -free [9]. Graphs of bounded maximum degree were subsequently characterized in terms of flexibility [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, in [2], Dvořák et al studied the 4-weighted flexibility of triangle-free planar graphs, and the result coincides with the choosability of triangle-free planar graphs. Later on, an interesting question is raised by Masařík [6] in the following.…”
Section: Introductionmentioning
confidence: 78%
“…Apart from the original paper introducing flexibility [10], where some basic results in terms of maximum average degree were established, the main focus in flexibility research has been on planar graphs. In particular, for many subclasses G of planar graphs, there has been a vast effort to reduce the gap between the choosability of G and the list size needed for flexibility in G. As of now, some tight bounds on list sizes are known: namely, triangle-free planar graphs [8], {C 4 , C 5 }-free planar graphs [20], and {K 4 , C 5 , C 6 , C 7 , B 5 }-free 1 planar graphs [16] are flexibly 4-choosable, and planar graphs of girth 6 [9] are flexibly 3-choosable. For other subclasses G of planar graphs, only an upper-bound is known for the list size k required for G to be flexibly k-choosable [6,18]; see [6] for a comprehensive overview and a discussion of the related results.…”
Section: W(v C)mentioning
confidence: 99%